Adolescent Sexual Behavior At High School Students YPPGI Pasirido Manokwari - Rasniah Sarumi; Sumaifah (Politeknik Karya Persada Muna, 2022)
Baground: Adolescence is a transition period from childhood to adulthood, where there are often problems with deviations in sexual behavior as a result of lack of knowledge about adolescent reproductive health, absorption of information through the media, the social environment and the role of parents as a control function. The purpose of this study was to determine the factors that influence the sexual behavior of students of YPPGI Pasirido Manokwari. Method: The type of research is quantitative with a cross sectional study design. This study was conducted at MA YPPGI Pasirido involving a population of 360 students and a sample of 78 people using purposive sampling techniques. The method of collection by distributing questionnaires and data collection techniques were carried out univariately and bivariately. Results: showing that adolescent knowledge has an influence/relationship with adolescent sex behavior, results of the Chi Square statistical test = 0.04, The media has an influence on adolescent sexual behavior, this is evidenced by adolescent sexual behavior, by the Chi Square statistical test = 0.00, The social environment has an influence with adolescent sexual behavior, by the Chi Square statistical test = 0.011, The role of parents has no influence on adolescent sexual behavior, by the Chi Square statistical test = 0.131. Conclusions: Based on the analysis data, it was concluded that of the four variables of adolescent knowledge, media, social environment and the role of parents, there are among one variable that does not have a significant relationship, including the role of parents. Keywords: Sexual behavior, media, adolescents